Factors influencing farmers' willingness to provide private land for a coordinated flood mitigation scheme in the Drin basin - Jan Brabec; Jan Macháč; András Kis; Gábor Ungvári (Journal of Flood Risk Management)
Abstract Flooding poses a significant and recurring threat in numerous regions. The adverse impacts of flooding can be mitigated through risk sharing, such as insurance or risk reduction. However, insurance might not be accessible in underdeveloped markets or in instances where floods are too frequent. Similarly, the necessary funding or land for structural measures might not be available. Alternatively, measures could be implemented on private land, either through individual initiatives or as part of a coordinated effort. This approach was explored in the flood‐prone regions of Albania and North Macedonia. A survey conducted among 124 farmers revealed that 73% of them are willing to allocate land for flood mitigation, provided they receive adequate compensation. Furthermore, certain factors increase farmers' willingness to cooperate. A logit model indicated a positive correlation between expectations of future floods (increased severity and frequency), receipt of ex‐ante financial support, positive perception of the effectiveness of agricultural flood mitigation measures, and age. Those who view flood protection as personal responsibility and those more inclined to pay for flood insurance are less likely to cooperate. The findings could be utilized to identify farmers who are likely to contribute to establishing a coordinated effort on a stable basis.